Representasi Maskulinitas Dalam Film Captain America: The First Avenger : Analisis Semiotika Charles Sanders Pierce - Erfina Nurussa'adah; Ramanda Fitrinasyah (Brand Communication, 2023)
This study aims to describe the representation of masculinity in the character of Steve Rogers in the film Captain America: The First Avenger which was released in 2011. This study reveals signs of masculinity in the character of Steve Rogers by using 7 concepts of masculinity by Janet Saltzman Chaftez which include appearance physical, functional, sexual, emotional, intellectual, interpersonal and personal characteristics. This research is a qualitative research with a descriptive approach. The objects in this study are the signs and meanings of Steve Rogers' masculinity in the scenes and dialogues in the film Captain America: The First Avenger. Data collection techniques were obtained through observation, documentation and textual analysis. This study uses Charles Sanders Pierce's semiotic analysis technique using the triadic model, namely representamen/sign, object and interpretant. This study obtained the results that the character of Steve Rogers had seven of the seven criteria of Janet Saltzman Chafetz's masculinity, which included (1) Physical Appearance: dashing, athletic, strong. (2) Functional, useful for relatives and their country. (3) Sexual, have an interest in the opposite sex and care for loved ones. (4) Emotions, able to control and hide the emotions he feels. (5) Intellectual, has a smart mind and is able to solve problems carefully. (6) Interpersonal, has the nature of great responsibility and has the soul of a leader. (7) Personal character, having an ambitious and unyieldingnature.